Penegakan Hukum Terhadap Anggota Militer Yang Melakukan Tindak Pidana Desersi di Wilayah Hukum Pengadilan Militer II-09 Bandung - Nurlaeli, Suci; Jaelani, Elan; Kholid, Muhamad (Lex Jurnalica, 2024)
Law enforcement of the crime of desertion at the Military Court II-09 Bandung is important to be carried out effectively and efficiently, this is because the crime of desertion in the jurisdiction of the Military Court II-09 Bandung is the highest military crime during 2020-2022 and almost every year there are remaining desertion cases that must be resolved in the following year. This study was conducted using an empirical legal method containing three main discussion points to measure the effectiveness of desertion law enforcement at the Military Court II-09 Bandung. The results of this study showed that the process of enforcing the crime of desertion at the Military Court II-09 Bandung had been carried out in accordance with laws and regulations starting from the administrative stage to the reading of the verdict. During 2020-2022, the process of enforcing the law on desertion at the Military Court II-09 Bandung was often hampered by the absence of witnesses and defendants at the trial. In reality, the obstacles that occur can be overcome effectively and efficiently by the Bandung Military Court II-09 by making various efforts depending on the constraints, including by conducting trials electronically, reading witness statements based on the BAP POM, transferring case files to a more authorized court, or by conducting trials in absentia.